Auditor Engagement Decision: An Exploratory Study in the Tunisian Context - Insaf Ouertani; Salma Damak Ayadi (Journal of Accounting and Management Information Systems (JAMIS), 2012)
This study seeks insights into the determinants of the acceptance decision made by Tunisian auditors. Through measurement scales of the auditors' perception of the decision's factors, the Factors Analysis highlights the decision's attributes. In our study, we used questionnaire surveys from 41 Tunisian auditors of 4 big affiliates and local audit firms. The results show that the audit Risk is the most important risk factor, followed by the client business Risk and finally the auditor's business Risk. Moreover, this study underlines the influence of investigation sources on this decision and the importance of the Risk Management Strategies in the compensation of the possible risks such as they were evaluated.
Keywords: M41; M42; 650; Client acceptance decision; engagement risk; factorial analysis; Tunisian context